Region : planning the future of the Twin Cities - Orfield, Myron; Luce, Thomas F. (University of Minnesota Press, 2009)
The Twin Cities region contains 11 counties, 300 cities and townships, and 1,700 unique combinations of tax rates and public services. Historically, this fragmentation has made it extremely difficult to address the social, economic, and environmental problems that affect all parts of the region, yet the Minneapolis and St. Paul area has generally been held in high esteem as a model of regional cooperation. How do policy planners make it work--and is it working well enough? In Region Myron Orfield and Thomas Luce examine both the successes and shortcomings of the Twin Cities Metropolitan Council.